ANÁLISE DAS CONDIÇÕES DE CONTORNO PARA SIMULAÇÃO E CONFIGURAÇÃO DE VENTILAÇÃO NATURAL EM PRÉDIO ESCOLAR - Freitas, Julye; Cunha, Eduardo; Leitzke, Rodrigo; Hax, Douglas; Duarte, Carolina; Carvalho, Amanda (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Natural ventilation is one of the main bioclimatic strategies to be used to provide thermal comfort, reduce thermal load in environments and reduce energy consumption. Therefore, this work aims to evaluate the boundary conditions of natural ventilation by means of computational simulation in the EnergyPlus 8.4 software in a school building. The thermal comfort in school environments is of great importance for a good performance of the students, who spend a long period of the day in school. The method consists of computational simulations of a school building considering different temperature setpoint variations for window opening (23ºC, 24ºC, 25ºC and 26ºC), window opening percentages (10%, 50% and 100%) and levels of infiltration (minimum, medium and maximum) in Brazilian bioclimatic zones 2 and 8. The results show that there is no significant difference between the different types of configuration in the same bioclimatic zone. In the bioclimatic zone 2, the greatest difference in thermal comfort per window opening percentage occurs at the 25 ° C setpoint at maximum infiltration with 0.05% variation. In the bioclimatic zone 8 the greatest difference is in the setpoint of 24ºC and minimum infiltration with 0.5% of variation.